Controlled trial of dexamethasone and mannitol for the cerebral oedema of fulminant hepatic failure. Issue 7 (July 1982) - Canalese, J; Gimson, A E; Davis, C; Mellon, P J; Davis, M; Williams, R
Abstract : A controlled trial of 44 patients was undertaken to evaluate the use of dexamethasone (32 mg stat, 8 mg qds) in preventing, and intravenous mannitol (1 g/kg) in reversing the cerebral oedema of fulminant hepatic failure. Diagnosis of cerebral oedema was based on intracranial pressure recordings or the presence of defined clinical signs. Cerebral oedema developed in 34 patients with similar frequency in those treated with and without dexamethasone (16 of 21 and 18 of 23 respectively). In those 34 patients episodes of cerebral oedema resolved significantly more frequently in the 17 patients who received mannitol than in the 17 patients who did not (44 of 53 and 16 of 17 respectively, p less than 0.001). Dexamethasone did not affect survival but among patients who developed cerebral oedema those who received mannitol had a significantly better survival than those who did not receive it (47.1% and 5.9% respectively, p 0.008, Fisher's one-tail test).